Exploring the nature of weak Chandra sources near the galactic centre - Bandyopadhyay, R; Blundell, K; Podsiadlowski, P; Miller-Jones, J; Wang, Q; Brandt, W; Rappaport, S; Pfahl, E (2004)
We present early results from the first near-IR imaging of the weak X-ray sources discovered in the recent Chandra/ACIS-I survey towards the Galactic Centre (GC) (Wang et al. 2002). These ̃800 discrete sources, which contribute significantly to the GC X-ray emission, represent an important and previously unknown population within the Galaxy. From our VLT observations we will identify likely IR counterparts to a sample of the hardest sources, which are most likely X-ray binaries. With these data we can place constraints on the nature of the discrete weak X-ray source population of the GC. Once the data analysis is complete we will discuss our results in the context of binary population synthesis models. © Copyright 2004: IA, UNAM.